Tujuh variasi snack berbahan pangan lokal untuk meningkatkan berat badan wanita premarital sebagai upaya mencegah kurang energi kronik - Marlynda Happy Nurmalita Sari; Dina Dewi Anggraini; Meirina Dwi Larasati; Indri Kusuma Dewi; Dewi Susilowati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: The prevalence of chronic energy deficiency among pregnant women in Indonesia remains relatively high, at 17.3%. If left untreated, chronic energy deficiency can cause health problems for both the mother and the fetus. Innovation is needed to provide supplementary food in the form of snacks made from local foods with a variety of variations for pregnant women to prevent chronic energy deficiency. Purpose: To determine the effect of seven variations of local food-based snacks on weight gain in pregnant women in an effort to prevent chronic energy deficiency. Method: This quantitative quasi-experimental study, with a single-group pretest-posttest design, was conducted in December 2025 at the Blora Community Health Center. The sampling technique used a total of 30 participants, divided into an intervention group and a control group. The independent variable in this study was snack provision, while the dependent variable was weight gain. Data analysis used univariate frequency distributions and bivariate Wilcoxon tests. Results: A significance value of 0.006 indicated a difference in weight gain between the intervention and control groups after the intervention. Conclusion: The intervention of providing seven snack variations to respondents resulted in a higher average weight gain compared to those who did not receive the seven snack variations. Keywords: Chronic Energy Deficiency; Local Snacks; Premarital Women.